2013
DOI: 10.1021/ja4068063
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Dominated Shape Recovery of Nanocrystals: A New Strategy for Trimetallic Catalysts

Abstract: Here we present a shape recovery phenomenon of Pt-Ni bimetallic nanocrystals that is unequivocally attributed to the defect effects. High-resolution electron microscopy revealed the overall process of conversion from concave octahedral Pt3Ni to regular octahedral Pt3Ni@Ni upon Ni deposition. Further experiments and theoretical investigations indicated that the intrinsic defect-dominated growth mechanism allows the site-selective nucleation of a third metal around the defects to achieve the sophisticated design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 25 publications
2
88
1
2
Order By: Relevance
“…Noble metal nanoparticles (NPs) have been extensively studied for various important applications such as fuel cells [1-], catalysis [4][5][6], surface enhanced Raman scattering (SERS), sensors [7], and biomedical applications [8]. From both experimental investigations on single crystal surfaces and theoretical studies, it has been widely reported that many physical and chemical properties are strongly dependent on the atomic arrangements and thus the crystallographic plane on the surface [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Noble metal nanoparticles (NPs) have been extensively studied for various important applications such as fuel cells [1-], catalysis [4][5][6], surface enhanced Raman scattering (SERS), sensors [7], and biomedical applications [8]. From both experimental investigations on single crystal surfaces and theoretical studies, it has been widely reported that many physical and chemical properties are strongly dependent on the atomic arrangements and thus the crystallographic plane on the surface [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the entropic negative contribution to the Gibbs free energy of mixing for the ternary system respect to the two binaries will favorably contribute to stability. So a number of reports have dealt with Pt-based ternary alloy nanoparticles for ORR 29-31, , but none has put effort in tailoring their morphological shape [32][33][34] . Now, on the basis of previous studies, Pt-Co binary alloy catalysts also exhibit high activity and stability [35][36][37][38] and for that reason, spherical PtNiCo ternary alloys have attracted more attention as a family of ORR catalysts that would allow tuning both ORR activity and stability [39][40][41][42] .…”
mentioning
confidence: 99%
“…55 In this case, the symmetry and registry are conserved across the interface, and only a slight lattice mismatch should be taken into account. This seems to be a common condition such that complex explanation can be avoided.…”
Section: Synthetic Methodologies Of Nhssmentioning
confidence: 99%
“…However, in real NPs, the perfect crystal planes, which are modeled by a vacuum slab, are usually not observed while some puckered or corrugated planes, such as edges and steps, are present on the interface. Li et al 55 reported the growth of Ni domains on concave Pt 3 Ni nanooctahedra ( Figure 5). The concaved Pt 3 Ni nanooctahedra Rational synthesis and structure-property relationships of NHSs B Xu et al were prepared by etching pre-existing PtNi nanooctahedra.…”
Section: Synthetic Methodologies Of Nhssmentioning
confidence: 99%
See 1 more Smart Citation